Enhancing Motivation among Online Distance Learning Students during the Covid-19 Pandemic in Malaysia - Zahir Osman; Shishi Kumar Piaralal; Nurliza Ahmad (2021)
The study was undertaken to assess the essential peer influence and tutor performance as key drivers in students’ motivation with the role of self-efficacy as a mediator in online distance learning higher education institutions in Malaysia during the Covid-19 pandemic. For data collection, the previously developed scales of peer influence, tutor performance, self-efficacy, and motivation in the context of online distance learning higher education institutions in Malaysia were distributed among the students in online distance learning higher education institutions. In total, 231 completed surveys were collected from the respondents and 12 outliers were detected through data screening using the Mahalanobis distance technique in SPSS, which left 219 clean data samples ready for analysis. The results from data analysis have shown that peer influence has no significant direct relationship with motivation but has significant indirect relationship with motivation, with self-efficacy as a mediator. Tutor performance has a significant direct relationship with motivation and also a significant indirect relationship with motivation, with selfefficacy as a mediator. Moreover, the implications of the findings were discussed, and future directions were recommended.